Molecular predictors of immunophenotypic measurable residual disease clearance in acute myeloid leukemia. Issue 1 (31st October 2022) - Stahl, Maximilian; Derkach, Andriy; Farnoud, Noushin; Bewersdorf, Jan Philipp; Robinson, Troy; Famulare, Christopher; Cho, Christina; Devlin, Sean; Menghrajani, Kamal; Patel, Minal A.; Cai, Sheng F.; Miles, Linde A.; et al.
Abstract: Measurable residual disease (MRD) is a powerful prognostic factor in acute myeloid leukemia (AML). However, pre‐treatment molecular predictors of immunophenotypic MRD clearance remain unclear. We analyzed a dataset of 211 patients with pre‐treatment next‐generation sequencing who received induction chemotherapy and had MRD assessed by serial immunophenotypic monitoring after induction, subsequent therapy, and allogeneic stem cell transplant (allo‐SCT). Induction chemotherapy led to MRD− remission, MRD+ remission, and persistent disease in 35%, 27%, and 38% of patients, respectively. With subsequent therapy, 34% of patients with MRD+ and 26% of patients with persistent disease converted to MRD‐. Mutations in CEBPA, NRAS, KRAS, and NPM1 predicted high rates of MRD− remission, while mutations in TP53, SF3B1, ASXL1, and RUNX1 and karyotypic abnormalities including inv (3), monosomy 5 or 7 predicted low rates of MRD− remission. Patients with fewer individual clones were more likely to achieve MRD− remission. Among 132 patients who underwent allo‐SCT, outcomes were favorable whether patients achieved early MRD− after induction or later MRD− after subsequent therapy prior to allo‐SCT. As MRD conversion with chemotherapy prior to allo‐SCT is rarely achieved in patients with specific baseline mutational patterns and high clone numbers, upfront inclusion of these patients into clinical trials should be considered.